The Precision and Accuracy of English Verbs Choice in Recount Text Written by the Students of CEC Denpasar: An Analysis of Metalanguage - Putri, Ni Nyoman Dewi Astari; Pastika, I Wayan; Satyawati, Made Sri (Yavana Bhasha : Journal of English Language Education, 2020)
This writing entitled â€œThe Precision and Accuracy of English Verbs Choice in Recount Text Written by The Students of CEC Denpasar: An Analysis of Metalanguageâ€ was conducted in order to be able to find out the percentage of precision and accuracy of English verbs choice in recount text written by the students of CEC Denpasar, analyze the lexico-semantic error, and describe the factors that cause this error. The data in this study were taken directly from recount texts written by the students of CEC Denpasar, interview, and questionnaire. Those data were collected by using a test, interview, and questionnaire method. The theory applied in this writing is Metalanguage from NSM theory proposed by Wierzbicka (1996). However, in describing the error, the analysis was done through configuration only by the qualitative method. The result shows that out of twenty-six verbs, twelve chosen verbs were less precise. Through Metalanguage, those errors can be described configurationally. Moreover, the difference between the error and the recommendation verbs can be explained, therefore, the difference can be shown. There were two factors that cause this error. They are external (teacher, method, strategy, technique used in teaching) and internal (motivation, potency, competence, and learnersâ€™ language background) factors.